COVID-19 vaccination knowledge, attitudes and practices among the general population of Romania during the third wave of COVID-19 pandemic - Armin Šljivo; Arian Abdulkhaliq; Nermir Granov; Leopold Reiter; Eljakim Mahendran; Ioannis Zeglis; Mohammed Abdulkadir Mohammed; Assy Yousef; Ilma Dadić; Katarina Ivanović; Amina Selimović; Ermina Mujičić; et al. (SAGE Open Medicine, 2023)
Objective: Romania began its COVID-19 immunization programme with approved vaccinations in three stages, as follows: The first step of vaccination is for health and social professionals, the second stage is for high-risk persons and the third stage is for the remainder of the general public. This study aims at assessment of knowledge, attitude and practice towards COVID-19 and vaccination against COVID-19 in the Romanian population during the third wave of the pandemic. Methods: This cross-sectional study was based on a Bosnian and Herzegovinian study on COVID-19 vaccination during the country’s third wave of COVID-19 pandemic. Results: Our study sample, dominantly female (629; 61.0%), with a bachelor’s degree (734; 71.2%), either single (539; 52.3%) or in a relationship (363; 35.2%), engaged in intellectual labour (910; 88.3%) and living in an urban environment (874; 84.8%) with a mean age of 25.07 ± 8.21 years, 294 (28.5%) people with COVID-19 symptoms and 86 (8.3%) were tested COVID-19 positive, had a mean knowledge score of 16.38 ± 4.0 with correct answer rates on questions ranging from 30.1% to 88.2%. Being single (odds ratio = 3.92, p  = 0.029) or in a relationship (odds ratio = 3.79, p  = 0.034), having a bachelor’s degree and higher (odds ratio = 1.61, p  = 0.006) and being COVID-19 tested (odds ratio = 1.82, p  < 0.001) were associated with higher knowledge test scores. Our sample had relatively optimistic attitudes towards final COVID-19 disease containment (712; 69.1%) and vaccination programmes (679; 65.9%). The majority of the sample followed socio-epidemiological measures and did not visit places of mass social gatherings (666; 64.1%) and wore masks (992; 95.7%) while being outside their home. In terms of vaccination rates, 382 (37.0%) of the individuals were presently immunized against COVID-19. Higher knowledge test scores (>15 points) (odds ratio = 1.66, p  = 0.002) and positive attitudes of this study (odds ratio = 1.59, p  = 0.001, odds ratio = 4.16, p  < 0.001) were identified as independent predictors for vaccinating against COVID-19. Conclusion: Romanian citizens have had good knowledge, optimistic attitudes and appropriate practices towards COVID-19 vaccination during the third wave of COVID-19 outbreak in the country. Higher knowledge regarding the disease and vaccination against it not only increased attitudes towards the end of the pandemic, but also increased the willingness to be vaccinated and to avoid infection risk factors.